2014
DOI: 10.1515/secm-2013-0316
|View full text |Cite
|
Sign up to set email alerts
|

The effect of zeolite particle modified by PEG on rubber composite properties

Abstract: The purpose of this paper was to investigate the surface modification of zeolite with polyethylene glycol (PEG) and the modified zeolite as a reinforcing filler partly replacing carbon black (CB) into rubber to prepare the rubber composites. The surface characteristics of zeolite modified by PEG and the unmodified zeolite were characterized by infrared (IR) spectroscopy and scanning electron microscopy (SEM). Moreover, the evaluations of the zeolite/rubber composite were carried out on characteristics such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Whereas, 10 phr unmodified zeolite gives the highest elongation and tear strength. This is in accordance with previous studies which found that CB substitution with 8 phr zeolite produced the best tensile strength (Fang et al, 2015). The modification of zeolite which does not show an enhancement of the mechanical properties is possible because physical modification just minimizes the size but does not makes a better bond between zeolite and the rubber matrix.…”
Section: Mechanical Propertiessupporting
confidence: 92%
See 2 more Smart Citations
“…Whereas, 10 phr unmodified zeolite gives the highest elongation and tear strength. This is in accordance with previous studies which found that CB substitution with 8 phr zeolite produced the best tensile strength (Fang et al, 2015). The modification of zeolite which does not show an enhancement of the mechanical properties is possible because physical modification just minimizes the size but does not makes a better bond between zeolite and the rubber matrix.…”
Section: Mechanical Propertiessupporting
confidence: 92%
“…Zeolites in nature are generally pure, easily available and inexpensive. It is widely used in the environmental, petroleum, chemical, and agricultural industries (Rianto et al, 2012;Wustoni et al, 2011;Fang et al, 2015). Nowadays, the zeolite is widely developed and investigated as a filler, such as for NR/NBR blend (Siriyong & Keawwattana, 2012), NBR (Petrova et al, 2015), NR (Pajarito et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of incorporating polymers and inorganic components into a material has been explored since the early industrialization of the polymers. Insertion of inorganic materials as fillers in the system could improve optical and mechanical properties [9]. The development of inorganic chemistry in recent decades and the introduction of the concept of "organic-inorganic hybrid materials" combined with multi-functionalization [10] has allowed the development of custom products.…”
Section: Introductionmentioning
confidence: 99%